Toward a Latino/a biblical interpretation - Lozada, Francisco, 1965- (Atlanta : SBL Press, 2017)
Engage an interdisciplinary approach In Toward a Latino/a Biblical Interpretation Francisco Lozada Jr. explores the complex and diverse issues related to Latino/a biblical interpretation. After laying the theoretical foundation, he offers three sample readings of biblical texts to lead readers through the intricacy of interpretation that has historically and culturally surrounded understanding what it means to do Latino/a biblical interpretation. Throughout, Lozada attempts to work out various strategies that Latinos/as have employed to read biblical texts. He argues that Latino/a biblical interpretation is concerned with identity and belongingness with a goal of transforming/liberating the Latino/a community. Features An introduction to what it means to do Latino/a biblical interpretation A demonstration of three different reading strategies (correlation, dialogical, and ideological) that Latinos/as employ in reading biblical texts An exploration of whether one has to be Latino/a to do Latino/a biblical interpretation.
Introduction: theorizing Latino/a biblical interpretation -- Toward Latino/a biblical studies: foregrounding identities and transforming communities -- Journeys and the Fourth Gospel: a correlation strategy -- Matthew 6:9b-13 (the Lord's Prayer): a dialogical strategy -- Galatians 2:11-14; an ideological strategy -- Conclusion: Latino/a biblical interpretation: is it a question of being and/or practice?
Includes bibliographical references and indexes.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; Latin America; Electronic books; Criticism, interpretation, etc